La ricerca tra innovazione, creatività e progetto / Research among Innovation, Creativity and Design - TARTAGLIA, ANDREA; BOLICI, ROBERTO; GAMBARO, MATTEO (Scuole di dottorato, 2012)
In the current socio-cultural scenario, the implementation of the university reform aimed at boosting third-level education calls for meditation within the discipline of Architectural Technology (ICAR 12). This review must address the research topics and academic profiles of PhD courses in the Technological Area, also in terms of fostering actions consistent with European strategic lines for the promotion of a knowledge society. Research, innovation, creativity and design are the keywords of this scenario that PhD students and lecturers must bear in mind when considering three fields of study: environmental design and landscape, building production and construction and works and services strategic for the community. This book "Research among innovation, creativity and design" develops the topics addressed during the VII OSDOTTA workshop (the network of PhD courses in the field of Architectural Technology) held at the Mantua campus of Milan Polytechnic on 15th-16th-17th September 2011.